2007
DOI: 10.1016/j.freeradbiomed.2007.06.021
|View full text |Cite
|
Sign up to set email alerts
|

The mode of cisplatin-induced cell death in CYP2E1-overexpressing HepG2 cells: Modulation by ERK, ROS, glutathione, and thioredoxin

Abstract: In a previous study, E47 HepG2 cells that overexpress human CYP2E1 were shown to be more sensitive to cisplatin than C34 cells that do not express CYP2E1. In this study, we found that this sensitivity was due to an earlier activation of ERK in the E47 cells than in C34 cells. Glutathione depletion by L-buthionine sulfoximine (BSO) enhanced cisplatin cytotoxicity via increasing production of reactive oxygen species (ROS) and activation of ERK. In contrast, elevation of glutathione by glutathione ethyl ester (GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 53 publications
3
20
0
Order By: Relevance
“…In previous studies, CDDP has been found to have an antiperoxidative effect on several tissues, such as the liver, kidney, and lens [35][36][37]. GSH is the most important molecule for maintaining cell integrity and participation in cell metabolism [38]. The role of GSH, which are non-protein thiols in the cells, in the formation of conjugates with electrophilic drug metabolites (most often formed by cytochrome P450-linked monooxygenase) is well established [39].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, CDDP has been found to have an antiperoxidative effect on several tissues, such as the liver, kidney, and lens [35][36][37]. GSH is the most important molecule for maintaining cell integrity and participation in cell metabolism [38]. The role of GSH, which are non-protein thiols in the cells, in the formation of conjugates with electrophilic drug metabolites (most often formed by cytochrome P450-linked monooxygenase) is well established [39].…”
Section: Discussionmentioning
confidence: 99%
“…GSH is the most important molecule for maintaining cell integrity and participation in cell metabolism [27]. The significant reduction in GSH levels promoted by CP represents an alteration in the cellular redox state, suggesting that the cells could be more sensitive to ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Since the oxidative stress is also related to the activation of ERK pathway [74,75], we tried to elucidate its involvement in the complex induced cytotoxic effects in osteoblasts as it has been previously reported for vanadate [57,74]. To achieve this aim we have used NAC and specific inhibitors of ERK pathway.…”
Section: Discussionmentioning
confidence: 99%